VARIASI BERAT KATALIS DAN SUHU REAKSI TRANSESTERIFIKASI CRUDE PALM OIL MENGGUNAKAN KATALIS CANGKANG KERANG DARAH KALSINASI 800 OC - Muhammad Reza Pahlevi; Nurhayati '; Sofia Anita (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
"> Biodiesel is one of the alternative fuels derived from petroleum. Compared to diesel fuel, it is renewable, biodegradable, and environmentally friendly. Biodiesel can be synthesized in two steps, that are esterification and transesterification stages. In this study, biodisel was synthesized from CPO through esterification using concentrated H2SO4 as catalyst, and transesterification using CaO catalyst from Anadara granosa shell waste. This catalyst was calcined at 800 oC for 10 hours. The surface area measurement of CaO catalyst derived blood clam shell was using methylene blue adsorption method and was obtained 17.3742 m2/g. The biodisel was synthesised with various of catalyst weight and reaction temperature. The result of biodiesel was obtained 76.40% with 4% CaO catalyst weight for 3 hours at ratio mol oil methanol 1:12 and reaction temperature at 65±2 °C.